Penggunaan Quiz Edukatif Sebagai Inovasi Pembelajaran untuk Meningkatkan Pemahaman Konsep Ekosistem - Siska Sari; Sulystiowati Sulystiowati (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
The use of innovative learning media is important in improving students’ understanding of ecosystem concepts in elementary science learning. However, science learning activities in elementary schools are still dominated by conventional teaching methods, causing students to become less active during lessons. This study aims to analyze the use of educational quizzes as a learning innovation to improve students’ understanding of ecosystem concepts. This research employed a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, documentation, and analysis of student quiz results. The findings indicate that educational quizzes were able to increase students’ enthusiasm, participation, concentration, and understanding of ecosystem materials such as food chains, food webs, producers, consumers, and decomposers. Students became more active in answering questions and showed higher motivation during the learning process. Educational quizzes also helped teachers evaluate students’ understanding more effectively and interactively. Therefore, educational quizzes can be used as an effective and enjoyable learning innovation to improve students understanding of ecosystem concepts in elementary science learning.